2017
DOI: 10.1186/s13063-017-2292-x
|View full text |Cite
|
Sign up to set email alerts
|

An optimized background regimen design to evaluate the contribution of levofloxacin to multidrug-resistant tuberculosis treatment regimens: study protocol for a randomized controlled trial

Abstract: BackgroundCurrent guidelines for treatment of multidrug-resistant tuberculosis (MDR-TB) are largely based on expert opinion and observational data. Fluoroquinolones remain an essential part of MDR-TB treatment, but the optimal dose of fluoroquinolones as part of the regimen has not been defined.Methods/designWe designed a randomized, blinded, phase II trial in MDR-TB patients comparing across levofloxacin doses of 11, 14, 17 and 20 mg/kg/day, all within an optimized background regimen. We assess pharmacokineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…The previously approved fluoroquinolones, levofloxacin and moxifloxacin, are now being evaluated in phase 2 trials designed at improving existing regimens for drug resistant disease. Three studies (MDR-END, OptiQ, and NEXT) containing levofloxacin (in combination with other drugs) in one or more of the treatment arms are active and recruiting patients with MDRTB [49]. All of these will be evaluating treatment success following 9–24 months of treatment with anticipated completion in 2019.…”
Section: Drugs and Drug Regimens Under Clinical Developmentmentioning
confidence: 99%
“…The previously approved fluoroquinolones, levofloxacin and moxifloxacin, are now being evaluated in phase 2 trials designed at improving existing regimens for drug resistant disease. Three studies (MDR-END, OptiQ, and NEXT) containing levofloxacin (in combination with other drugs) in one or more of the treatment arms are active and recruiting patients with MDRTB [49]. All of these will be evaluating treatment success following 9–24 months of treatment with anticipated completion in 2019.…”
Section: Drugs and Drug Regimens Under Clinical Developmentmentioning
confidence: 99%
“…Other inclusion criteria included known HIV status (regardless of result and therapy), a weight of Ն40 kg, and a Karnofsky Performance Status score of Ͼ60. Full details of eligibility criteria and trial design are available in the published protocol (10). All study treatment doses were directly observed.…”
mentioning
confidence: 99%
“…Even if dysglycaemia has not been an issue for levofloxacin as for gatifloxacin, and there may be less problems than for moxifloxacin with regard to QT-prolongation and drug-drug interactions (192), less is known about tolerability and safety of higher than recommended doses of levofloxacin (70,193). A randomised ongoing dose-ranging study (OptiQ trial; NCT01918397) evaluating the contribution of levofloxacin to MDR-TB treatment, will present data on correlations of levofloxacin dose increments (11,14,17 and 20 mg/kg) and potential favourable treatment outcome without increased risk of toxicity (194). Until more evidence on safety and clinical outcome data is available, it may be wise to avoid using levofloxacin in case of low-level resistance mediated by mutations such as A90V, S91P or D94A, even if the MIC value is in the suggested ATU that technically is just below the current critical concentration (70,92).…”
Section: Is Re-evaluation Of Breakpoints For M Tuberculosis Accordinmentioning
confidence: 99%